DAMPAK PENGGUNAAN SERIOUS GAME DAN GAME EDUKATIF PADA PEMBELAJARAN PEDAGOGI ANAK SEKOLAH DASAR: LITERATURE REVIEW - Wahyu Agung Prasetyo; Namora; Joni Karnando; Silvia Netri Azhari; Anita, Sri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Serious game and educational game technology is currently widely available in app stores, and is often used for classroom learning for research or production purposes. This study will focus on the impact of using serious games and educational games for pedagogical learning and the health aspects that follow. The creativity that has been created can answer the challenges of children's diverse intelligence. Games can certainly be used to facilitate children's diverse intelligence and provide tasks by utilizing adequate visuals, audio, and illustrations. Several studies related to pedagogical learning from teachers still have gaps in guiding and giving assignments to children, this creates a gap where educational games can be used as learning media aimed at pedagogy. This study uses a literature review method to obtain an overview of the benefits and risks that follow the use of gadgets in games. Article data sources come from SINTA, IEEE Xplore, Springer Link, Sciencedirect, ACM, digital libraries, and Scopus.